Acid/Base‐Triggered Switching of Circularly Polarized Luminescence and Electronic Circular Dichroism in Organic and Organometallic Helicenes. Issue 4 (21st November 2014) - Saleh, Nidal; Moore, Barry; Srebro, Monika; Vanthuyne, Nicolas; Toupet, Loïc; Williams, J. A. Gareth; Roussel, Christian; Deol, Kirandeep K.; Muller, Gilles; Autschbach, Jochen; Crassous, Jeanne
Abstract Electronic circular dichroism and circularly polarized luminescence acid/base switching activity has been demonstrated in helicene‐bipyridine proligand 1 a and in its "rollover" cycloplatinated derivative 2 a. Whereas proligand 1 a displays a strong bathochromic shift (>160 nm) of the nonpolarized and circularly polarized luminescence upon protonation, complex 2 a displays slightly stronger emission. This strikingly different behavior between singlet emission in the organic helicene and triplet emission in the organometallic derivative has been rationalized by using quantum‐chemical calculations. The very large bathochromic shift of the emission observed upon protonation of azahelicene‐bipyridine 1 a has been attributed to the decrease in aromaticity (promoting a charge‐transfer‐type transition rather than a π–π* transition) as well as an increase in the HOMO–LUMO character of the transition and stabilization of the LUMO level upon protonation.